Al-Qur'an Murottal Therapy as Anxiety Management for Mothers with Children Suffering from Cancer: A Case Report - Rahma Elfa Aulia; Henny Yulianita; Maria Komariah (Universitas Duta Bangsa Surakarta, 2026)
Introduction: A childhood cancer diagnosis causes mothers to experience a variety of emotional reactions, including anxiety. This anxiety is due to high emotional distress and a very heavy burden. Therefore, it is important as a nurse to provide appropriate self-intervention in overcoming such anxiety. Nurses can implement one of the anxiety management interventions by using Qur'anic murottal therapy. Objectives: This study aims to determine the Effectiveness of the Application of Qur'anic Murottal Therapy as Anxiety Management in Mothers with Cancer Children in the Pediatric Inpatient Room at X Hospital. Methods: This research design uses a case study approach (Case Report) with descriptive methods and observation techniques, interviews, then analyzed with the Man, Material, Method (3M) analysis approach. The instrument used to assess the level of anxiety is the STAI-T Instrument. The sample in this study was mothers with cancer children in X Hospital, totaling 1 person. Results: The first day before the intervention the family's anxiety was at a score of 54 (Severe anxiety) and after the intervention was at a score of 51 (Severe anxiety), and on the fourth day after the intervention was at a score of 24 (Not anxious). The results of the 3M aspect review showed that nurses had not implemented Qur'anic murottal therapy as an option for family anxiety management interventions in the room. Conclusion: The application of anxiety management with Qur'anic murottal therapy to the patient's family is effective in reducing anxiety. This therapy can be an option to overcome anxiety in families of pediatric patients with cancer.